PENGARUH FUNGSI MENTORING TERHADAP KEINGINAN BERPINDAH DENGAN PERSEPSI DUKUNGAN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. BANK ACEH SYARIAH KANTOR PUSAT OPERASIONAL BANDA ACEH - Fauzan Adhima, Lenny Rakhmawati (Departemen Manajemen, 2018)
This study aims to determine the effect of mentoring function to turnover intention with perceived organizational support as a mediating. The empirical study conducted at PT. Bank Aceh Syriah Kantor Pusat Operasional Banda Aceh staff used a questionnaire as a research instrument, which samples in this study of 120 people. Probability sampling is used as a sampling technique with Total Smpling. Methods HLM (Hierarchical Linear Modelling) is used as a method of data analysis using software IBM SPSS 20. These results indicate that the mentoring function significant impact on turnover intention, perceived organizational support significantly related to turnover intention, mentoring function significant impact on perceived organizational support and in addition showed that the perceived organizational support mediates the significantly effect of mentoring function to turnover intention.Keywords : Mentoring Function, Perceived Organizational Support, and Turnover Intention.